Moraxella catarrhalis decreases antiviral innate immune responses by down‐regulation of TLR3 via inhibition of p53 in human bronchial epithelial cells. Issue 6 (15th March 2016) - Heinrich, Annina; Haarmann, Helge; Zahradnik, Sabrina; Frenzel, Katrin; Schreiber, Frauke; Klassert, Tilman E.; Heyl, Kerstin A.; Endres, Anne‐Sophie; Schmidtke, Michaela; Hofmann, Jörg; Slevogt, Hortense
ABSTRACT: Chronic obstructive pulmonary disease (COPD) is complicated by infectious exacerbations with acute worsening of respiratory symptoms. Coinfections of bacterial and viral pathogens are associated with more severe exacerbations. Moraxella catarrhalis is one of the most frequent lower respiratory tract pathogens detected in COPD. We therefore studied the impact of M. catarrhalis on the antiviral innate immune response that is mediated via TLR3 and p53. Molecular interactions between M. catarrhalis and normal human bronchial epithelial (NHBE) cells as well as Beas‐2B cells were studied using flow cytometry, quantitative PCR analysis, chromatin immunoprecipitation, RNA interference, and ELISA. M. catarrhalis induces a significant down‐regulation of TLR3 in human bronchial epithelial cells. In M. catarrhalis ‐infected cells, expression of p53 was decreased. We detected a reduced binding of p53 to the tlr3 promoter, resulting in reduced TLR3 gene transcription. M. catarrhalis diminished the TLR3‐dependent secretion of IFN‐β, IFN‐λ, and chemokine (C‐X‐C motif) ligand 8. In addition in M. catarrhalis infected cells, expression of rhinovirus type 1A RNA was increased compared with uninfected cells. M. catarrhalis reduces antiviral defense functions of bronchial epithelial cells, which may increase susceptibility to viral infections.—Heinrich, A., Haarmann, H., Zahradnik, S., Frenzel, K., Schreiber, F., Klassert, T. E., Heyl, K. A., Endres, A.‐S., Schmidtke, M., Hofmann, J., Slevogt, H. Moraxella catarrhalis decreases antiviral innate immune responses by down‐regulation of TLR3 via inhibition of p53 in human bronchial epithelial cells. FASEB J. 30, 2426–2434 (2016). www.fasebj.org